POLITIK HUKUM DALAM KEBIJAKAN PENANGGULANGAN DEEPFAKE POLITIK ANCAMAN BARU TERHADAP INTEGRITAS DEMOKRASI - Imam Fathwa; Mustofa Kamil; Bayu Triwibowo; Tri Susanto; Ratu Chumairoh Noor; Dian Retno Widayati (Berajah Journal, 2026)
Advances in artificial intelligence (AI) technology have given rise to the phenomenon of deepfakes, which pose a serious threat to the integrity of democracy. Political deepfakes—the manipulation of video, audio or images of political figures using AI technology—are capable of creating highly convincing fake content that is difficult to distinguish from the original. This phenomenon threatens the foundations of democracy, which are built upon the truthfulness of information and public trust in the political process. This study aims to analyse legal policy in the context of countering political deepfakes using a normative-empirical legal research method. The findings indicate that the existing legal framework in Indonesia is insufficient to comprehensively address the threat of political deepfakes. Effective legal policy must be progressive, integrating aspects of technology regulation, the protection of human rights, and the strengthening of public digital literacy. This study recommends the establishment of specific regulations governing the use of AI technology in a political context through a multi-stakeholder approach.